Freedom of Establishment and Freedom of Capital Movement as a Limitation to Excessive Regulation of the Financial Market - Mariański, Michał (PRAWO i WIĘŹ, 2024)
This paper aims to analyze the interconnection between the regulation of the financial market and the principles of freedom of establishment and freedom of capital movement. In particular, the author seeks to determine whether the aforementioned principles can limit the EU legislator in the way he attempts to regulate the financial sector. This question is of significant importance, as protectionist phenomena are increasingly visible in the EU, especially in times of crises such as the pandemic or the war in Ukraine. The existence of freedom of establishment and freedom of capital movement has a positive impact on the development of the internal market, as it protects cross-border investors from excessive national regulation. However, the author would like to underline that this also constitutes a regulatory challenge for the legislator who wants to introduce certain restrictions or a certain higher level of supervision on the financial market. Consequently, it can be posited that the freedoms that define the EU internal market are a further rationale for the existence of the so-called incomplete law on the financial markets, given that this specific sector cannot be fully regulated at the national and supranational level. In this context, this article may serve as a catalyst for initiating a discourse on the responsiveness of national and European legislators in times of financial crises and the efficacy of financial market regulation.